Assessment of Serum Procalcitonin as a Biomarker of Bloodstream Infection & Focal Bacterial Infection in Febrile Patients - Amith. N; Sabu Augustine (Asian Journal of Medical Research, 2020)
Background: To assess serum procalcitonin as a biomarker of bloodstream infection & focal bacterial infection in febrile patients. Subjects and Methods: Seventy- six adult patients presenting with fever (temperature >38 degree) were selected for the study. Imaging such as chest radiograph, ultrasonography (USG) of abdomen, computed tomography (CT) and magnetic resonance imaging were performa. Serum PCT levels were measured. Results: Aetiological diagnosis was evident focus of infection without bacteraemia in 24, dengue in 3, malaria in 3, scrub typhus in 1, leptospirosis in 6, bacteraemia in 8, other causes (non-infectious) in 1 and undiagnosed in 40 cases. Cause for evident focus of infection without bacteraemia was cellulitis in 3, UTI in 4, pneumonia            in 7, TB in 3, pylonephritis in 2, bacterial in 1, viral              in 1, acute meningitis in 1, acute gastroenteritis in 1 and swine flu in 1 patient. The difference was significant (P< 0.05). The mean PCT level in malaria patients was 5.7 ng/ml, in bacteremia was 8.2 ng/ml, in leptospirosis was 0.9 ng/ml, in dengue was 0.5 ng/ml, in scrup typhus was 0.7 ng/ml and in evident cause of infection cases was 3.4 ng/ml. The difference was significant (P< 0.05). Conclusion: Serum PCT level might be a useful biomarker for identifying bacteraemia as well as predicting mortality in patients with acute fever requiring admission to hospital.